Testing the market efficiency in Indian stock market: evidence from Bombay Stock Exchange broad market indices - Elangovan, Rajesh; Irudayasamy, Francis Gnanasekar; Parayitam, S. (Universidad ESAN. ESAN Ediciones, 2022)
Purpose: Despite volumes of research on the efficient market hypothesis (EMH) over the last six decades, the results are inconclusive as some studies supported the hypothesis, and some studies rejected it. The study aims to examine the market efficiency of the Indian stock market. Design/methodology/approach: For analysis, nine Bombay Stock Exchange (BSE) broad market indices were selected covering the study period from 01 January 2011 to 31 December 2020. The data collected for this study are daily open, high, low and closing prices of selected indices. The tools used in this study are: (1) unit root test to check the stationarity of time series, (2) descriptive statistics, (3) autocorrelation and (4) runs test. Findings: The empirical findings of the study reveal that BSE broad market indices do not follow a random walk and Indian stock market is as weak-form inefficient. Research limitations/implications: The findings from this study provide several avenues for future research. One of the research implications is that anomalies in the statistical results by different academicians in the finance area need to be explained by future researchers. Practical implications: Investment companies need to understand that extraordinary skills are required to beat the market to make abnormal returns. In an inefficient market where securities do not reflect the complete available information, it is challenging for the investment brokers to convince the customers about the portfolios they recommend to the public that the rate of return would be more than expected. Social implications: As economic growth is related to the growth in the financial sector, developing countries like India depend on the accuracy of the information. In the presence of asymmetric information, the fluctuations in the stock market would have serious harmful consequences on the economy. Originality/value: Amid several controversies surrounding the EMH testing, this study is a modest attempt to provide evidence that the Indian stock market is in weak-form inefficient. However, it is essential to link investors' behaviour and trends observed in the financial sector to fully understand the implications of EMH.

Propósito: A pesar de los volúmenes de investigación sobre la hipótesis del mercado eficiente (EMH) durante las últimas seis décadas, los resultados no son concluyentes ya que algunos estudios apoyaron la hipótesis y otros la rechazaron. El estudio tiene como objetivo examinar la eficiencia del mercado de valores de la India. Diseño/metodología/enfoque: para el análisis, se seleccionaron nueve índices de mercado amplios de la Bolsa de Valores de Bombay (BSE) que cubren el período de estudio desde el 1 de enero de 2011 hasta el 31 de diciembre de 2020. Los datos recopilados para este estudio son los precios diarios de apertura, máximo, mínimo y cierre. de índices seleccionados. Las herramientas utilizadas en este estudio son: (1) prueba de raíz unitaria para verificar la estacionariedad de series de tiempo, (2) estadística descriptiva, (3) autocorrelación y (4) prueba de corridas. Hallazgos: Los hallazgos empíricos del estudio revelan que los índices de mercado amplios de la BSE no siguen un paseo aleatorio y que el mercado de valores indio es igualmente ineficiente en su forma débil. Limitaciones/implicaciones de la investigación: Los hallazgos de este estudio proporcionan varias vías para futuras investigaciones. Una de las implicaciones de la investigación es que los futuros investigadores deben explicar las anomalías en los resultados estadísticos de diferentes académicos en el área de finanzas. Implicaciones prácticas: las empresas de inversión deben comprender que se requieren habilidades extraordinarias para ganarle al mercado y obtener retornos anormales. En un mercado ineficiente donde los valores no reflejan toda la información disponible, resulta difícil para los corredores de inversiones convencer a los clientes acerca de las carteras que recomiendan al público de que la tasa de rendimiento sería superior a la esperada. Implicaciones sociales: Como el crecimiento económico está relacionado con el crecimiento del sector financiero, los países en desarrollo como la India dependen de la exactitud de la información. En presencia de información asimétrica, las fluctuaciones del mercado de valores tendrían graves consecuencias perjudiciales para la economía. Originalidad/valor: en medio de varias controversias en torno a las pruebas EMH, este estudio es un modesto intento de proporcionar evidencia de que el mercado de valores indio es débil e ineficiente. Sin embargo, es esencial vincular el comportamiento de los inversores y las tendencias observadas en el sector financiero para comprender plenamente las implicaciones de la EMH.
Keywords: Efficient market hypothesis; Unit root; Hipótesis del mercado eficiente; ADF test; Raíz unitaria; Autocorrelation; Prueba ADF; Autocorrelación; Indian stock market; Mercado de valores indio; https://purl.org/pe-repo/ocde/ford#5.02.04